Socio-culturally responsive differentiated instruction in EFL classrooms: The mediating role of UDL in enhancing students’ higher-order thinking skills - Muhamad Yahrif; Suharti Siradjuddin (Universitas Islam Malang, 2026)
This study investigates the effectiveness and underlying mechanisms of socio-culturally responsive differentiated instruction in English as a foreign language (EFL) classrooms within the Merdeka Belajar curriculum. Although differentiated instruction has been widely adopted, its integration with students’ socio-cultural backgrounds and its contribution to higher-order thinking skills remain underexplored. This study integrates differentiated instruction, socio-cultural learning theory, and universal design for learning (UDL) within a quantitative explanatory design. Data were obtained from junior secondary students through academic records (n = 239) and survey responses (n = 184) and analyzed using the Wilcoxon Signed-Rank Test and partial least squares structural equation modeling (PLS-SEM). The findings show a significant improvement in students’ academic achievement following the implementation of socio-culturally responsive differentiated instruction (p < .001, r = .86). Motivation and engagement, and the relevance and contextual adaptation of learning significantly enhanced students’ understanding, which subsequently supported higher-order learning skills and learning satisfaction. Understanding and learning outcomes also mediated the relationships between the instructional predictors and higher-order outcomes. The findings suggest that meaningful EFL learning can be strengthened when differentiated instruction is responsive to learners’ socio-cultural contexts and supported by flexible and accessible learning pathways. The study contributes an integrated model for inclusive, context-sensitive, and cognitively enriching EFL practice, while acknowledging the need for validation across broader and more diverse settings.